COMPARISON AND IMPLICATIONS FROM STRIKINGLY DIFFERENT AUTHIGENIC CARBONATES IN A NYEGGA COMPLEX POCKMARK, G11, NORWEGIAN SEA - Mazzini A.; Svensen H.; Planke S.; Hovland M. (My University, 2006)
Authigenic carbonates sampled in a complex pockmark (G11) from the Nyegga area, south western Vøring Basin, reveal strikingly different morphologies. A comparative study of macro and micro features of these neighbouring samples was approached in order to attempt a reconstruction of the pockmark dynamics. The carbonate morphologies include thin (~ 1 cm) platy carbonate crusts, blocky and massive carbonate ridges up to several metres in size, and irregularly shaped carbonate deposits consisting of interconnected tubular and uneven intervals displaying high porosity. Our observations indicate that three distinct mechanisms of fluid seepage and carbonate precipitation occurred within the pockmark. Petrography studies reveal that the samples contain three generations of predominantly aragonitic cements. In addition, zoned crystals with coexisting Mg-calcite and dolomite are abundant in one sample suggesting a trend of gradual increase of the sulphate concentrations in the pore fluids during carbonate precipitation. Isotope measurements on bulk carbonate cements show consistent values with δ13C as low as - 52.1‰, δ18O as high as 6.4‰, and 87/86Sr of 0.7092. Anaerobic oxidation of methane close to seafloor conditions can explain these isotope data. The carbonates have a common carbon source despite the differences in morphology. Methane probably originated from the dissolution of gas hydrates as supported from calculated 18O enrichment in the pore fluids and the methanogenic carbon. We propose a model where the differences in bulk carbonate morphology are related to local sediment properties, depth of carbonate precipitation and the flow rate of the seeping fluids. © 2006 Elsevier B.V. All rights reserved.
Keywords: CARBONATES; GAS HYDRATES; HYDROCARBON SEEPAGE; POCKMARK; VøRING PLATEAU